The Identification Procedure for the Constitutive Model of Elasto-Viscoplasticity Describing the Behaviour of Nanocrystalline Titanium - NOWAK, Zdzisław; PERZYNA, Piotr (Engineering Transactions, 2014)
The main objective of the present paper is the description of the behaviour of the ultrafine-grained (UFG) titanium by the constitutive model of elasto-viscoplasticity with the development of the identification procedure. We intend to utilize the constitutive model of the thermodynamical theory of elasto-viscoplasticity for description of nanocrystalline metals presented by Perzyna (2010) [1]. The identification procedure is based on experimental observation data obtained by Jia et al. (2001) [13] for ultrafine-grained titanium and by Wang et al. (2007) [17] for nanostructured titanium. Hexagonal close-packed (hcp) ultrafine-grained titanium processed by sever plastic deformation (SPD) has gained wide interest due to its excellent mechanical properties and potential applications as biomedical implants.